10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Aim To explore the effect of psychological contract on turnover intention among young nurses and to investigate the mediating roles of psychological capital and job performance. Background The high turnover rate of young nurses poses a significant risk to the stability of the nursing workforce and organizational effectiveness. Although psychological contract has been recognized as an important factor influencing employee retention, how it affects turnover intention in young nurses remains underexplored. Methods A cross-sectional survey was conducted among young nurses working in hospitals. Standardized questionnaires were used to assess psychological contract, psychological capital, job performance, and turnover intention. A mediation model was established to examine the direct and indirect relationships among the variables. Results A higher perceived level of psychological contract fulfillment was associated with lower turnover intention among young nurses. Higher levels of psychological capital and better job performance were also associated with lower turnover intention. Psychological capital and job performance partially mediated the relationship between psychological contract and turnover intention. Discussion The findings highlight the importance of psychological and performance factors in understanding turnover intention. Psychological contract fulfillment was positively associated with enhanced intrinsic motivation and professional identity, which in turn corresponded to improved job performance and reduced turnover intention. Conclusion Psychological contract is a key correlate of turnover intention in young nurses, and it is associated with turnover intention through the mediating roles of psychological capital and job performance. Implications for nursing Interventions that strengthen psychological support, enhance confidence and resilience, and promote performance development may be associated with reduced turnover intention among young nurses. Implications for nursing policy Healthcare institutions should prioritize policy initiatives that meet the psychological expectations of young nurses, support their career development, and reinforce a retention-oriented management system to stabilize the nursing workforce.